Automated Fault Control Panel during Serial Production Equipment of Defense Industry Technology - Ibragimov, R.A.; Svikhnushin, N.M.; Zeynalova, A.E. (Herald of Azerbaijan Engineering Academy, 2022)
The paper focuses on the control panel for checking the correct functioning of one of the specific mass-produced electronic samples of special equipment of defense industry technology. The rationale for the expediency of designing a control panel using the principles of modularity and the use of built-in control and measurement tools were given. A functional diagram, design features of a simple-to-manufacture, small-sized and low-cost control panel, developed by the authors and implemented in production, with a description of its operating modes were given. In addition to the control panel includes the hardware, special software that automatically controls (or step by step) the entire procedure for monitoring, measuring, visualizing and archiving test results.